Livestock-Associated MRSA CC1 in Norway; Introduction to Pig Farms, Zoonotic Transmission, and Eradication - Elstrøm, Petter; Grøntvedt, Carl Andreas; Gabrielsen, Christina; Stegger, Marc; Angen, Øystein; Åmdal, Solfrid; Enger, Hege; Urdahl, Anne Margrete; Jore, Solveig; Steinbakk, Martin; Sunde, Marianne (Frontiers in Microbiology, 2019)
Abstract Farm animals have been identified as an emerging reservoir for transmission of livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) to humans. The low incidence of MRSA in humans and farm animals in Norway has led to the implementation of a national strategy of surveillance and control of LA-MRSA aiming to prevent livestock becoming a domestic source of MRSA to humans. In 2015, MRSA clonal complex 1 spa-type t177 was identified in nine Norwegian pig herds in two neighboring counties. An outbreak investigation was undertaken, and measures of control through eradication were imposed. We performed a register-based cohort study including pig herds and MRSA-positive persons in Norway between 2008 and 2016 to investigate the livestock-association of MRSA CC1, the transmission of the outbreak strain to humans before and after control measures, and the effect of control measures imposed. Data from the Norwegian Surveillance System of Communicable Diseases were merged with data collected through outbreak investigations for LA-MRSA, the National Registry and the Norwegian Register for Health Personnel. Whole-genome sequencing was performed on isolates from livestock and humans identified through contact tracing, in addition to t177 and t127 isolates diagnosed in persons in the same counties. It is likely that a farm worker introduced MRSA CC1 to a sow farm, and further transmission to eight fattening pig farms through trade of live pigs confirmed the potential for livestock association of this MRSA type. The outbreak strain formed a distinct phylogenetic cluster which in addition to the pig farms included one sheep herd and five exposed persons. None of the investigated isolates from possible cases without direct contact to the MRSA positive farms were phylogenetically related to the outbreak strain. Moreover, isolates of t177 or t127 from healthcare and community-acquired cases were not closely related to the outbreak cluster. Eradication measures imposed were effective in eliminating MRSA t177 from the positive pig holdings, and the outbreak strain was not detected in the national pig population or in persons from these counties after control measures.